Representation of Environmental Issues in Marjan’s "Baruna the Guardian of the Ocean" Ad 2023 Episode 1 and 2 (Analysis Semiotika Charles Sanders Peirce) - Mahruf, Fatimah Nur Aliya; Boer, Kheyene Molekandella; sucipta, Johantan Alfando Wikandana; Agustian, Jaka Farih (Jurnal Indonesia Sosial Sains, 2024)
Environmental issues have become the talk of recent years, education and information about deteriorating natural conditions are needed to maintain natural health. Given the rise of environmental issues in recent years, PT Lasallefood Indonesia has participated by raising environmental issues as their advertising concept for 2023. This study aims to show environmental issues in the form of marine pollution represented in marjan advertisements "baruna sang guardian samudra" episodes 1 and 2 using qualitative approaches and data collection techniques Observation and documentation. The analysis was conducted by observing scenes related to marine pollution obtained through symbols and signs displayed throughout the marjan advertisement "Baruna the Guardian of the Ocean" episodes 1 and 2 through the approach of Charles Sanders Pierce's Semiotic Theory. The results of this study show that the Baruna Sang Guardian of the Ocean marjan advertisement tries to represent 3 aspects broadly related to environmental issues of marine pollution, the first is the act of marine pollution represented by adult characters who are fishermen and children as coastal villagers who throw plastic waste into the sea, the second is the impact of plastic pollution on the marine environment represented by the inner ocean and the surface that has been Filled with plastic waste, the last impact of marine pollution that is happening to marine life is represented by the figure of a dragon as marine life affected by marine pollution in the form of being eaten by plastic waste.